Enhancing gutta-percha with silver mesoporous calcium silicate nanoparticles for advanced endodontic applications - Amer A. Mohammed; Ahmed H. Ali; Federico Foschi; Francesco Mannocci (PLoS ONE, 2025)
Aim This study aimed to develop a modified gutta-percha (GP) multifunctional endodontic material by incorporating mesoporous calcium silicate nanoparticles (MCSNs) or silver-incorporated mesoporous calcium silicate nanoparticles (Ag-MCSNs) as bioactive nanoparticle fillers to enhance bioactivity, biomineralization, and radiopacity while achieving low cytotoxicity and improved antibacterial activity. Methodology MCSNs and Ag-MCSNs were synthesized and incorporated into GP at concentrations of 1%, 5%, and 10% by weight. The chemical and structural characterization of the new GP materials was performed using Fourier-transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), energy-dispersive spectrometry (EDS), and field emission-scanning electron microscopy (FE-SEM) to assess filler distribution. Biomineralization was evaluated using XRD, EDS, and scanning electron microscopy (SEM). Ion release, pH changes, MTT assays, and culture-based techniques were employed to assess bioactivity, biocompatibility, and antibacterial properties. Finally, radiopacity testing was conducted. Results All samples of the newly developed GP exhibited uniform particle distribution within the GP matrix. Bioactivity and biomineralization tests revealed hydroxyapatite (HA) layer precipitation at 3, 7, 14, and 28 days, with maximum HA formation observed with prolonged immersion. Samples containing MCSNs or Ag-MCSNs created a weakly alkaline microenvironment initially, maintaining a suitable pH over time. All groups demonstrated non-cytotoxicity, with cell viability exceeding 70%. Antibacterial tests showed larger inhibition zones in all experimental groups compared to the control, with GP containing 10% MCSNs or Ag-MCSNs exhibiting the highest antibacterial activity, particularly Ag-MCSNs. Radiopacity tests indicated no significant difference between the experimental and control groups. Conclusion Gutta-percha materials incorporated with 10% MCSNs or Ag-MCSNs demonstrated enhanced bioactivity, biomineralization, and antibacterial properties compared to the control GP, while maintaining suitable levels of biocompatibility in accordance with ISO 10993/2009 standards. The incorporation of Ag-MCSNs significantly improved antibacterial effects, particularly against Enterococcus faecalis, and increased radiopacity, making it a promising material for root canal therapy.